2014
DOI: 10.1002/cpt.19
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Pharmacological Treatment of Neuropathic Pain

Abstract: Patients with the same disease may suffer from completely different pain symptoms yet receive the same drug treatment. Several studies elucidate neuropathic pain and treatment response in human surrogate pain models. They show promising results toward a patient stratification according to the mechanisms underlying the pain, as reflected in their symptoms. Several promising new drugs produced negative study results in clinical phase III trials. However, retrospective analysis of treatment response based on base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 80 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…[1][2][3][4] Although many pharmacotherapies (eg, gabapentin, pregabalin, and duloxetine) are effective in managing pain, drugs have adverse effects. 5,6 Therapeutic ultrasound (TU), a noninvasive method, is used in the treatment of carpal tunnel syndrome (CTS), the most common entrapment neuropathy. 7,8 There is a growing body of evidence that TU treats neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Although many pharmacotherapies (eg, gabapentin, pregabalin, and duloxetine) are effective in managing pain, drugs have adverse effects. 5,6 Therapeutic ultrasound (TU), a noninvasive method, is used in the treatment of carpal tunnel syndrome (CTS), the most common entrapment neuropathy. 7,8 There is a growing body of evidence that TU treats neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Also, the noninvasive TU was often used in treating CTS, one of the most frequently compressive neuropathy. 5,6 However, it is unclear whether TU could treat persistent postoperative pain evoked by thoracotomy with rib retraction and the role of TU in its improvement. We showed that TU (1.0 W/cm 2 ) did reduce the persistent neuropathic pain, but the benefit was observed early and did not return to those of sham-operated animals.…”
Section: Discussionmentioning
confidence: 99%
“…‘Omics’ and other emerging biomarker data combined with computational tools for exploring large datasets suggest how much more patient information can be utilized to deliver more customized care in general [14] and in neuropathic pain in particular [15]. Ongoing efforts strive to identify psychosocial variables that could be used to identify patient subgroups [16] as well, even if the end goal of fully personalized or precision medicine cannot be achieved in the short term [5].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, sciatica and chronic back pain are the most common types of neuropathic pain, and the pathogenesis is complicated (2). The primary causes are the degeneration of the corresponding organs, lumbar disc herniation caused by trauma, nerve damage, calcification of ligaments, bone hyperplasia, inflammation and tumors (3)(4)(5). Due to the long period of clinical treatment, disease recurrence and poor prognosis, the quality of life of patients with neuropathic pain is greatly affected.…”
Section: Introductionmentioning
confidence: 99%